Independent Role of Left Ventricular Global Longitudinal Strain in Predicting Prognosis of Chronic Heart Failure Patients. Issue 7 (14th March 2013) - Iacoviello, Massimo; Puzzovivo, Agata; Guida, Pietro; Forleo, Cinzia; Monitillo, Francesco; Catanzaro, Raffaella; Lattarulo, Maria Silvia; Antoncecchi, Valeria; Favale, Stefano
<x xml:space="preserve">Abstract</x> Aims To evaluate the independent prognostic role of two‐dimensional (2D) strain measures reflecting global longitudinal left ventricular (LV) systolic function in outpatients affected by chronic heart failure (CHF). Methods and results Global longitudinal LV systolic strain (GLS) was assessed in 308 outpatients affected by CHF, by analyzing standard views with 2D speckle tracking technique. During a mean follow‐up of 26 ± 13 months 37 patients died (29 due to cardiovascular causes), 10 patients underwent heart transplantation, and 75 patients experienced at least 1 episode of hospitalization due to acute decompensated heart failure (ADHF). Thirty‐one patients without a history of major ventricular arrhythmic events experienced the occurrence of ventricular fibrillation and/or tachycardia or sudden death was observed. Multivariate Cox regression analysis showed that GLS was significantly associated with all‐cause mortality (HR: 1.15; 95%CI: 1.02–1.30; P: 0.026), cardiovascular death (HR: 1.20; 95%CI: 1.04–1.39; P: 0.011), cardiovascular death or heart transplantation (HR: 1.24; 95%CI: 1.09–1.41; P: 0.001), ADHF‐related hospitalizations (HR: 1.15; 95%CI: 1.05–1.25; P: 0.003), and arrhythmic events (HR: 1.17; 95%CI: 1.03–1.33; P: 0.018). Conclusions Quantifying LV longitudinal systolic function in CHF outpatients on the basis of 2D speckle tracking analysis provides a new parameter that independently predicts patient outcome, thus, strengthening its possible role in current clinical practice.